Maternal infection during pregnancy and type 1 diabetes mellitus in offspring: a systematic review and meta-analysis. Issue 16 (28th December 2018) - Yue, Y.; Tang, Y.; Tang, J.; Shi, J.; Zhu, T.; Huang, J.; Qiu, X.; Zeng, Y.; Li, W.; Qu, Y.; Mu, D.
Abstract: Previous studies have demonstrated that type 1 diabetes mellitus (T1DM) could be triggered by an early childhood infection. Whether maternal infection during pregnancy is associated with T1DM in offspring is unknown. Therefore, we aimed to study the association using a systematic review and meta-analysis. Eighteen studies including 4304 cases and 25 846 participants were enrolled in this meta-analysis. Odds ratios (ORs) and 95% confidence intervals (CIs) were synthesised using random-effects models. Subgroup analyses and sensitivity analyses were conducted to assess the robustness of associations. Overall, the pooled analysis yielded a statistically significant association between maternal infection during pregnancy and childhood T1DM (OR 1.31, 95% CI 1.07–1.62). Furthermore, six studies that tested maternal enterovirus infection showed a pooled OR of 1.54 (95% CI 1.05–2.27). Heterogeneity from different studies was evident ( I 2 = 70.1%, P < 0.001) and was mainly attributable to the different study designs, ascertaining methods and sample size among different studies. This study provides evidence for an association between maternal infection during pregnancy and childhood T1DM.